(6x-7)(6x+7)=

Simple and best practice solution for (6x-7)(6x+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6x-7)(6x+7)= equation:


Simplifying
(6x + -7)(6x + 7) = 0

Reorder the terms:
(-7 + 6x)(6x + 7) = 0

Reorder the terms:
(-7 + 6x)(7 + 6x) = 0

Multiply (-7 + 6x) * (7 + 6x)
(-7(7 + 6x) + 6x * (7 + 6x)) = 0
((7 * -7 + 6x * -7) + 6x * (7 + 6x)) = 0
((-49 + -42x) + 6x * (7 + 6x)) = 0
(-49 + -42x + (7 * 6x + 6x * 6x)) = 0
(-49 + -42x + (42x + 36x2)) = 0

Combine like terms: -42x + 42x = 0
(-49 + 0 + 36x2) = 0
(-49 + 36x2) = 0

Solving
-49 + 36x2 = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '49' to each side of the equation.
-49 + 49 + 36x2 = 0 + 49

Combine like terms: -49 + 49 = 0
0 + 36x2 = 0 + 49
36x2 = 0 + 49

Combine like terms: 0 + 49 = 49
36x2 = 49

Divide each side by '36'.
x2 = 1.361111111

Simplifying
x2 = 1.361111111

Take the square root of each side:
x = {-1.166666667, 1.166666667}

See similar equations:

| 5+-= | | Log(3)5-log(3)x=log(3)2 | | (2x-2)(4x+8)= | | 375=15s+75 | | 5x+6-3x-3=6 | | 7(2a-4b)-3(4a-2b)= | | P+30.34= | | 3x^2-6x+4=13 | | 6x+3(2x+8)=120 | | 8x=2+y | | (22b-1)-7(3b+3)=-6 | | 5x(2x^2-3x+3)= | | C=15s+75 | | =90-70 | | 2y^2-y-36=0 | | 2x+25=3 | | 8x(9x+5)= | | 6s-17=-8+3s | | x*87=87 | | 3k+15-9=2(1k+2) | | 6r-15=0+r | | 5x-3(x-1)=7 | | 7-3x+5when=2 | | x(x+40)=180 | | 6p+5[3(2-3p)-2(5-4p)]= | | -42=7(8-x) | | (3x-5)+(6x-40)=90 | | (3x-5)+(6x-40)= | | -7x+10=10-7x | | 4a^2-17a-15=0 | | -5y^2+8y+7=0 | | 45/6b+4111/140=4/5b-22/5+11/7 |

Equations solver categories